RANCANG BANGUN OIL SKIMMER MACHINE UNTUK PEMBERSIH TUMPAHAN OLI - Novangga Tri Putranto; Bayu Wiro Karuniawan; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
In this modern era waste oil is very influential when the production goes to the bar production company or others. Water is very widely used for the cooling process of products. In the waste pool there is a mixture of water and oil waste. Mixing oil with water must be separated, because if not separated oil can clog the waterways. In addition, if oil is still mixed with water it can reduce the nature of the water used for cooling bar products.Required the right method or method to separate oil from mixed water, namely with an oil skimmer engine that can separate oil with mixed water. The results of the design of the oil skimmer engine are the frame, base frame, base set of the gearbox motor, base house bearing, bottom roller adjust, and the shaft and roller on the machine using ASTM A36 and Stainless Steel materials. Special flat belt on the machine using polymeric materials. The transmission is driven by a 0.25 hp AC motor that is connected directly to the upper roller shaft. The method used in making this oil skimmer machine is the product design and development method. The performance of the oil skimmer engine can separate oil as much as 408.51 ml / minute.